Dynamic shifts in the organization of primary somatosensory cortex induced by bimanual spatial coupling of motor activity - Schaefer, Michael; Flor, Herta; Heinze, Hans-Jochen; Rotte, Michael (NeuroImage, 2005)
Previous work has shown that training and learning can induce powerful changes in the homuncular organization of the primary somatosensory cortex (SI). Moreover, a number of studies suggest the existence of short-term adaptation of representational maps in SI. Recently, motor activity has been shown to induce rapid modulation of somatosensory cortical maps. It is hypothesized that there is a task-related influence of motor and premotor areas upon the organization of somatosensory cortex. In order to test this hypothesis, we studied the functional organization of somatosensory cortex by examining coupling effects in a bimanual movement task. Bimanual coupling is known to be related to an activation of the premotor cortex and the supplementary motor area. The functional organization of the somatosensory cortex for known bimanual coupling effects was compared to the organization of the somatosensory cortex during the same movements but with only a small effort in coupling. Topography of the functional organization of the somatosensory cortex was assessed using neuromagnetic source imaging based on tactile stimulation of the first (D1) and fifth digit (D5). We could show that the cortical representations of D1 and D5 moved further apart during the bimanual coupling task in comparison to the same task without coupling and rest. Our data suggest that somatosensory cortical maps undergo fast and dynamic modulation as a result of a task-related influence of motor or premotor areas.